2015
DOI: 10.3928/1081597x-20150424-01
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability Data and Agreement of Keratometry With the VERION System Compared to the IOLMaster

Abstract: he exact measurement of the radius of the curvature of the cornea is crucial for planning the diopter of the intraocular lenses (IOLs) for implantation during cataract surgery. The error in measurements of the keratometric data can lead to unwanted postoperative refractive error. Although keratometric mistakes are not the first or most frequent source of error in today's biometric methods, 1 keratometry has an undisputed and important role in cataract surgery. Moreover, cases of implantation of toric IOLs requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
(18 reference statements)
3
16
0
1
Order By: Relevance
“…They found that the SMI Reference Unit, LenStar, and IOL master devices all had comparable reliability in providing accurate K-values measurements. Additionally, Nemeth et al27 reported that VERION has high repeatability and agreement with the IOL master.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the SMI Reference Unit, LenStar, and IOL master devices all had comparable reliability in providing accurate K-values measurements. Additionally, Nemeth et al27 reported that VERION has high repeatability and agreement with the IOL master.…”
Section: Discussionmentioning
confidence: 99%
“…The Verion Image Guided System has been shown to have high repeatability [4], and recently it has also been shown that, its use resulted in less postoperative deviation from target-induced astigmatism and showed less postoperative toric IOL misalignment than using a manual-marking technique [5]. Therefore, it is a candidate to have an increasing role in cataract surgery planning, especially in toric IOL patients and for limbal relaxing incisions.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, there is only one study which analyzed the repeatability of keratometric and white-to-white distance measurements with the Verion Measurement Module in 50 eyes of 50 healthy volunteers [4]. The measurements were also compared with the IOLMaster in the same study.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated the number of pairs needed to detect a true difference in population means (δ) with type I error probability α given a standard deviation (σ). Specifically, for a statistical power of 80 per cent, considering δ and σ reported comparing the Verion system and the optical biometer system IOLMaster, and an α error of 0.05, the sample size required was 53 eyes.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, only one study to date has evaluated the intra‐session repeatability of keratometric astigmatism obtained with the Verion System (Alcon Laboratories Inc., Fort Worth, Texas, USA), with an analysis of the interchangeability of such measurement with that provided by the IOLMaster optical biometer. The aim of our study was to evaluate in healthy eyes the intra‐session repeatability of point‐based keratometric readings and astigmatism value obtained with the Verion system.…”
mentioning
confidence: 99%